Directions for educational development in the Year of the Teacher and Tutor - Veriaskina A. N., Sabodina E. P., Dzokaeva Z. M., Pokhilko A. D., Gubanova M. A., Sian I., Vlasova S. A., Dormidontov R. A., Omarov O. M., Ismailov S. O., Annaev R. I., Narykova O. N., Liakhova E. G., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Petrova N. G., Pogosian S. G., Zaritskaia V. V., Koreneva A. V., Ryzhkova I. V., Denisova O. A., Lekhanova O. L., Gudina T. V., Glukhova O. A., Bukin D. A., Zinin S. V., Tkachenko I. S., Panteleeva N. G. (Directions for educational development in the Year of the Teacher and Tutor, 2023)
the period of student life makes great demands on young people who are not yet always ready for psychological stresses, changed stereotype and lifestyle associated with higher education. Therefore, it is important to study various features of the psychological status of students taking into account the nature of the future profession. The study of a number of psychological characteristics among undergraduate nursing students showed that 55.6% of them had an average level of empathy. Type B stress tolerance (corresponding to optimal) was noted in 38.3% of the students. Self-esteem was adequate only in 16.7% of cases. The majority (73.2%) of students had a high level of tension of psychological defense.
Keywords: самооценка; эмпатия; empathy; self-esteem; психологическая защита; бакалавры сестринского дела; cтрессоустойчивость; bachelors of nursing; stress resistance; psychological defense